A scoping review of vulvodynia research: Diagnosis, treatment, and care experiences - Athina Zoi Lountzi; Purva Abhyankar; Hannah Durand (Women's Health)
Background: Vulvodynia is a significant genital pain condition, affecting an estimated 10% to 28% of individuals worldwide. Its multifactorial etiology, diagnostic challenges, and limited treatment options contribute to its substantial personal and socioeconomic burden. Despite its prevalence, vulvodynia remains under-recognized and under-researched, necessitating a comprehensive review of existing evidence to inform future research strategies. Objective: This scoping review examines the extent and nature of clinical and psychosocial research on vulvodynia, with a focus on diagnosis, treatment, healthcare access, and its impact on quality of life, psychological well-being, and intimate relationships. Eligibility Criteria: Eligible studies included primary research using quantitative, qualitative, or mixed methods designs, as well as systematic, scoping, and topical reviews. Studies were included if they examined clinical or psychosocial aspects of vulvodynia. Research on other types of vulvar pain, animal studies, neurobiological research, and studies from non-high-income countries were excluded. Sources of Evidence and Methods: A systematic search of Medline, PubMed, CINAHL, PsycINFO, and Cochrane was conducted in March 2024 using predefined search terms related to vulvodynia, diagnosis, treatment, and patient experiences. Review findings, limitations, and recommendations were extracted to provide an overview of existing research, mapping methodologies, measures, and key findings of primary studies on vulvodynia. Results: A total of 144 articles were included, comprising 21 reviews and 123 primary studies. Clinical research primarily addressed diagnosis, risk factors, and comorbidities, while treatment studies evaluated pharmacological therapies, psychological therapies, laser therapy, physiotherapy, acupuncture, and multidisciplinary approaches. Psychosocial research focused on patient experiences, psychosocial factors, and barriers to care. However, methodological limitations, inconsistent measurement tools, limited patient involvement, and study heterogeneity challenge the generalizability of findings. Conclusions: This review highlights critical gaps in vulvodynia research. Despite considerable research efforts, vulvodynia remains poorly understood. Addressing methodological weaknesses and involving patients more robustly in research design are essential to advance knowledge and improve care outcomes in vulvodynia.